DIFFICULTIES IN TEACHING GERMAN MODAL VERBS TO ECONOMICS STUDENTS - Adina SĂCARA-ONIŢA; Andra-Teodora PORUMB (Annals of the University of Oradea: Economic Science)
Modal verbs are an important chapter in learning German. The paper presents how the modal verbs are thought to the economics students in our university, emphasizing the common mistakes of the students and possible measures the teacher should take in order to diminish the number of learning mistakes. The first part of the paper deals with the theoretical background, thus being such a difficult subject for the Romanian student, the paper brings up even the conjunction differences on this subject, dealing with different verbal tenses in the German grammar. The second part of this paper presents a text full of modal verbs, in different tenses, the students are asked to recognize them. In the paper I will show the mistakes the students usually make and the proportion of the right answers at this task. The following part deals with different exercises, in order to conclude the mistakes and the proportion of the right answers at this challenge. The final part shows the conclusions of this study that reflects on the results of the conducted measurements. The modal verbs play an important role in facilitating an efficient and understandable communication pattern in the society and therefore, they form significant aspect in the human language. Modal verbs add to the text precision and clearance in its meaning.